CAR-T cell therapy followed by allogenic hematopoietic stem cell transplantation yielded comparable outcome between Ph like ALL and other high-risk ALL - Hai-ping Dai; Dan-qing Kong; Hong-jie Shen; Wei Cui; Qian Wang; Zheng Li; Jia Yin; Li-qing Kang; Lei Yu; De-pei Wu; Xiao-wen Tang (BMC, 2023)
Abstract It was previously believed that patients with Ph-like ALL had poorer prognosis compared with other B-ALL subgroups due to resistance to conventional chemotherapy and lack of targeted drugs. CAR-T therapy has been successfully applied in the treatment of relapsed and refractory B-ALL. Currently, there are few data on whether CAR-T therapy can alter the outcome of Ph-like ALL. Here we included 17 Ph-like, 23 Ph+ and 51 other B-ALL patients, who received autologous CAR T-cell therapy and subsequently allogenic stem cell transplantation. Patients in the Ph-like group and B-ALL-others group were younger that those in the Ph+ group (P=0.001). Ph-like and Ph+ ALL patients showed higher white blood cell counts at diagnosis (P=0.025). The percentage of patients with active disease before receiving CAR T-cells infusion was 64.7%, 39.1% and 62.7% in the Ph-like, Ph+ and B-ALL-others groups. The response rates to CAR-T therapy were 94.1% (16/17), 95.6% (22/23) and 98.0% (50/51) in the Ph-like, Ph+ and B-ALL-others groups. Measurable residual disease negative CR was achieved in 64.7% (11/17), 60.9% (14/23) and 54.9% (28/51) in the Ph-like, Ph+ and B-ALL-others groups, respectively. The estimated rates of 3-year overall survival (65.9%±16.5%, 59.7%±10.5% and 61.6%±7.3%, P=0.758) and 3-year relapse-free survival (59.8%±14.8%, 63.1%±10.5% and 56.3%±7.1%, P=0.764) were comparable among the Ph-like, Ph+ and B-ALL-others groups. Estimated 3-year cumulative relapse rate was 7.8%±0.6%, 23.4%±0.9% and 29.0%±0.4% (P=0.241). Our findings suggest that CART followed by allo-HSCT results in a comparable prognosis in Ph-like ALL and other high-risk B-ALL. Trial registration ClinicalTrials. gov, NCT03275493, Registered on September 7, 2017, prospectively registered and NCT03614858, Registered on August 3, 2018, prospectively registered.